Pendampingan Ibu Hamil dan Implementasi Pemanfaatan Herbal sebagai Upaya Perlindungan dari Covid 19 - Alfiah Rahmawati; Atika Zahria Arisanti (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Pregnancy is a period that is eagerly awaited because this period greatly determines the quality of human resources and the future of the fetus in the womb will greatly determine the development of the child in the future. One of the factors that affect the health of the mother and the fetus is the nutrition obtained during pregnancy. During pregnancy, health problems that occur during pregnancy can affect the health of the fetus in the womb until the birth and growth of the baby. One of the causes is nutritional factors in pregnancy which can affect immunity / immunity in pregnant women. In the era of the Covid-19 pandemi, pregnant women have a higher risk of developing serious disease morbidity and mortality compared to the general population which can result in fetuses in the form of preterm labor and fetal distress in pregnant women who are infected with Covid-19 so that they must be delivered by cesarean delivery. One of the efforts to realize the health of pregnant women in preventing the most common pregnancy problems is anemia with non-pharmacological treatment by consuming beets and dates as well as increasing knowledge of pregnant women about pregnancy examinations during the Covid-19 pandemi as an effort to monitor maternal welfare and fetus. The implementation of activities with the application of science and technology which is carried out twice a month with the target of pregnant women at Limbangan Public Health Center, Kendal Regency. The form of science and technology transfer begins with a pretest and ends with a post test, then a demonstration of making beat fruit juice, and distributing 7 dates of dates and education about Covid-19 in pregnant women and a question and answer session. The most important thing in this activity is that pregnant women are able to make beat fruit juice and consume dates as well as an understanding of ANC examinations during a pandemi.